Improving environmental performance through innovative commercial leasing - Bright, S; Roussac, C (Emerald Group Publishing, 2012)
The purpose of this paper is to illustrate, by reference to practical examples, how leases of commercial buildings can be more responsive to environmental issues. It explains how difficult it is within the structure and content of conventional leases to reduce the environmental impact of the tenanted commercial built environment. It explores the interplay between the content and structure of commercial leases and the behaviour of building owners, managers, tenants and occupants, illustrated through the experiences of a large Australian-based commercial office building owner/operator.